A Cd/Zn Co-hyperaccumulator and Pb accumulator, Sedum alfredii, is of high Cu tolerance. (August 2020) - Xv, Lingling; Ge, Jun; Tian, Shengke; Wang, Haixin; Yu, Haiyue; Zhao, Jianqi; Lu, Lingli
Abstract: High sensitivity towards Cu toxicity is problematic when using some hyperaccumulator plants for phytoremediation of soils with mixed contamination of Cu. Sedum alfredii, a Cd/Zn co-hyperaccumulator and Pb accumulator, is widely used for remediation of Cd, Zn, and Pb co-contaminated soils in China. In this paper, the tolerance and accumulation ability of S. alfredii towards Cu stress and its potential for phytoremediation of multi-metal polluted soils have been studied. Both the hyperaccumulating ecotype (HE) and non-hyperaccumulating ecotype (NHE) of S. alfredii accumulated high Cu in the roots and translocated minimal Cu to the shoots, and Cu in the stems and leaves mostly restricted in the vascular tissues (phloem zone). The HE plants, however, exhibited high Cu resistance with stimulated lateral root growth and increased chlorophyll content under 10 μM Cu treatment. XANES analysis showed that Cu in HE roots comprised Cu 2+ (46.7%), Cu-histidine (35.2%) and Cu-cell wall (18.1%). The NHE under Cu stress showed decreased biomass, reduced leaf chlorophyll content, altered root architecture, and higher Cu localized to root cell wall as compared with the HEs. Potted HE plants thrived six months in multi-metal contaminated soils including 3897 mg kg −1 available Cu. In conclusion, HE S alfredii is highly tolerant toward Cu due to metal homeostasis in root cells. Therefore, this plant has great potential to remediate Zn, Cd, and Pb contaminated soils those also contain high levels of Cu. Graphical abstract: Image 1 Highlights: A Cd/Zn co-hyperaccumulator and Pb accumulator  Sedum alfredii  is highly tolerant towards Cu toxicity. High Cu tolerance in  S. alfredii  is associated with Cu homeostasis in root cells rather than root-to-shoot translocation. Sedum alfredii plants may be useful for remediating Zn, Cd, and Pb from soils co-contaminated with high Cu. Abstract : Capsule: The Cd/Zn co-hyperaccumulator and Pb accumulator Sedum alfredii demonstrates great root tolerance and high shoot growth under Cu stress, which may facilitate its potential usage for remediation of Zn, Cd, and Pb from soils co-contaminated with high Cu.